EFFECTIVENESS OF MODERN TECHNOLOGIES OF INFORMATION TRAINING (Intent Research Scientific Journal, 2023)
The need to use digital technologies in remote learning for these students provides statistics on the need to use digital technology, the advantages and the use of distance learning, and the need to use digital technology and introduce a new generation of systems of distance learning, and that it is faster, easier and cheaper to learn new skills or topic-related materials through a distance learning system. It also provides suggestions and recommendations on solving problems and solutions that hinder the effective implementation of distance education in our country using digital technologies.